1973
DOI: 10.1111/j.1471-4159.1973.tb07531.x
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase a Activities in Normal and Sectioned Rat Sciatic Nerve

Abstract: Abstract— The phospholipase A1 (EC 3.1.1.32) and A2 (EC 3.1.1.4) activities of rat sciatic nerve homogenates have been studied. With phosphatidylcholine as substrate normal nerve had significant activity of both types at pH 5.0. Substantial increases occurred in nerve undergoing Wallerian degeneration after transection, beginning as early as 2 days after operation and rising to eight times normal values by the second week.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

1977
1977
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 17 publications
2
19
0
Order By: Relevance
“…Significant phospholipase A, and A2 activities, at pH 5.0 in the homogenate of rat whole sciatic nerve have also been reported by Webster [1973], who suggested that both types of enzyme were associated, at least in part, with Schwann cells.…”
Section: Discussionmentioning
confidence: 53%
“…Significant phospholipase A, and A2 activities, at pH 5.0 in the homogenate of rat whole sciatic nerve have also been reported by Webster [1973], who suggested that both types of enzyme were associated, at least in part, with Schwann cells.…”
Section: Discussionmentioning
confidence: 53%
“…An increase in Iysolecithin in transected cat nerve was reported by Berryet al (1965), while Domonkos and Heiner (1968) found an increase in Iyso "cephalin." Webster (1973) observed substantial increases of phospholipases Al and A 2 in rat sciatic nerve beginning as early as 2 days after section and rising to 8 times normal values by the 2nd week. He suggested that Iysophosphatides may be active as solubilizing agents.…”
Section: Peripheral Nervous Systemmentioning
confidence: 78%
“…On the other hand, Schwann cells destined to form myelin internodes continue to divide, transferring axons to their progeny after each division until they invest a single axon. When the diameter of the single axon reaches 1-2 J.Lm, PNS myelination is ready to commence (Peters and Vaughn, 1970;Webster, 1971;Martin and Webster, 1973;Webster et al, 1973).…”
Section: Myelinogenesis In the Peripheral Nervous Systemmentioning
confidence: 99%
“…An increase in lysolecithin in transected cat nerve has been reported by Berry et al (1965), while Domonkas and Heiner ( 1968) found an increase in lyso-"cephalin," presumably lysoethanolamine plasmalogen. Webster ( 1973) observed substantial increases of phospholipases A1 and A2 in rat sciatic nerve beginning as early as 2 days after section and rising to eight times normal values by the second week, and suggested that lysophosphatides may be active as solubilizing agents in the demyelination process.…”
Section: Cell-mediated Secondary Demyelinationmentioning
confidence: 92%
“…On the other hand, Schwann cells destined to form myelin internodes continue to divide, transferr:ng axons to their progeny after each division until they invest a single axon with a diameter of about 2 p.m. Under such circumstances, PNS myelination is ready to commence (Peters and Vaughn, 1970;Webster, 1971;Martin and Webster, 1973;Webster et al, 1973).…”
Section: Myelinogenesismentioning
confidence: 99%